Taxonomic review of Athliini (Coleoptera: Scarabaeidae: Melolonthinae), a new tribe of scarab beetles endemic to South America - Smith, Andrew B.t.; Evans, Arthur V. (Zootaxa, 2018)
Athliini Smith & Evans, new tribe (Coleoptera: Scarabaeidae: Melolonthinae) includes four genera that occur from southern South America through to the southeastern regions of Brazil: Apteroathlia Smith & Evans, new genus, Athlia Erichson, 1835, Dihymenonyx Gutiérrez, 1949, and Ulata Saylor, 1945. Justifications are provided for the new tribe and for the placement each genus in the new tribe. Keys to genera and species are presented along with distributional data and maps for all species. Apteroathlia translucida Smith & Evans, new species and Apteroathlia nox Smith & Evans, new species are described. Lectotypes are designated for Athlia bruchi Moser, 1924 and Athlia rustica Erichson, 1835. A neotype is designated for Ulata argentina Saylor, 1945.